Synthesis and biological activity of a new class of antitumor cyclopeptides based on the solomonamides - Cheng-Sánchez, Iván; Carrillo Fernández, Paloma; Martínez-Póveda, Beatriz Amparo; Rodríguez-Quesada, Ana María; Medina-Torres, Miguel Ángel; Sarabia-García, Francisco Ramón (My University, 2018)
Solomonamides A (1) and B (2) are novel natural products recently isolated from the marine sponge Theonella swinhoei [1]. Preliminary structural studies revealed an unprecedented cyclic peptide type structure. Interestingly, solomonamide A exhibits anti-inflammatory activity, showing potent reduction (60%) of inflammation at a very low concentration of 100 µg/kg in animal models. However, the scarcity of these compounds from their natural sources has been a drawback for further pharmacological assays. In fact, the anti-inflammatory activity of solomonamide B was not evaluated due to the limited amounts. This difficulty to access large amounts of these compounds makes quite difficult to gain insight into their biological profiles and mechanism of action and justifies the chemical synthesis of this new class of cyclic peptides. As a consequence, the solomonamides have been the subject of several synthetic efforts [2] notably by the Reddy group who has recently reported the first total synthesis of solomonamide B based on a intramolecular Heck reaction, which led to a revision of the initially proposed structure for 2 [3].
Keywords: Productos naturales; Total synthesis; Natural products; Antitumoral; Solomonamides; Ring-closing metathesis